Variable stiffness Mckibben muscles with hydraulic and pneumatic operating modes. (2nd July 2016) - Xiang, Chaoqun; Giannaccini, Maria Elena; Theodoridis, Theo; Hao, Lina; Nefti-Meziani, Samia; Davis, Steven
Abstract: McKibben muscles have been shown to have improved stiffness characteristics when operating hydraulically. However when operating pneumatically, they are compliant and so have potential for safer physical human–robot interaction. This paper presents a method for rapidly switching between pneumatic and hydraulic modes of operation without the need to remove all hydraulic fluid from the actuator. A compliant and potentially safe pneumatic mode is demonstrated and compared with a much stiffer hydraulic mode. The paper also explores a combined pneumatic/hydraulic mode of operation which allows both the position of the joint and the speed at which it reacts to a disturbance force to be controlled.